Anthocyanins and proanthocyanidins from blueberry–blackberry fermented beverages inhibit markers of inflammation in macrophages and carbohydrate‐utilizing enzymes in vitro. Issue 7 (25th March 2013) - Johnson, Michelle H.; de Mejia, Elvira Gonzalez; Fan, Junfeng; Lila, Mary Ann; Yousef, Gad G.
<x xml:space="preserve">Abstract</x> Scope Berries are an excellent source of dietary flavonoids which have several health benefits. Methods and results We evaluated well‐characterized anthocyanins (ANCs) and proanthocyanidins (PACs) from fermented blueberry–blackberry beverages. Wines were produced from highbush blueberries and blackberries grown in Illinois and blended to create ratios ranging from 100% blueberry to 100% blackberry. Total ANCs of the wine were strongly correlated to total phenolics (r = 0.99, p < 0.05) and to antioxidant capacity (r = 0.77, p < 0.05). ANC‐ and PAC‐enriched fractions were purified from each wine blend and a phenolic profile was generated. ANCs increased with more blackberries from 1114 to 1550 mg cyanidin‐3‐O‐glucoside (C3G) equivalents/L. Hydrolysable tannins were identified in the PAC‐enriched fraction. Both ANC‐ and PAC‐enriched fractions inhibited starch‐degrading enzyme α‐glucosidase and dipeptidyl peptidase‐IV activity. Computational docking demonstrated that delphinidin‐3‐arabinoside effectively inactivated dipeptidyl peptidase‐IV by binding with the lowest interaction energy (−3228 kcal/mol). ANC and PAC (100 μM C3G and epicatechin equivalents, respectively) from blueberry–blackberry blends reduced LPS‐induced inflammatory response in mouse macrophages via the nuclear factor kappa B‐mediated pathway. Conclusion ANC‐ and PAC‐ (including hydrolysable tannins in blackberry) enriched fractions from blueberry and blackberry fermented beverages are beneficial sources of antioxidants, inhibitors of carbohydrate‐utilizing enzymes, and potential inhibitors of inflammation.